A new dendrobatid frog (Anura: Dendrobatidae: Colostethus) from Aprada tepui, southern Venezuela - Barrio-Amorós, César L. (Zootaxa, 2006)
A new species of Colostethus is described from Venezuelan Guayana. It inhabits the slopes of Aprada tepui, a sandstone table mountain in southern Venezuela. The new species is distinguished from close relatives by its particular pattern, absence of fringes on fingers, presence of a lingual process, and yellow and orange ventral coloration. It is the 18 th described species of Colostethus from Venezuelan Guayana.